The emerging role of glycine receptor α2 subunit defects in neurodevelopmental disorders - Fraser, Sean D.; Harvey, Robert J. (Frontiers in Molecular Neuroscience, 2025)
Rare neurodevelopmental disorders (NDDs) are one of the most significant unmet challenges in healthcare due to their lifelong nature, high management costs, and recurrence within families. This review will focus on newly-emerging genetic forms of NDDs resulting from variants in the glycine receptor (GlyR) α2 subunit gene. Studies using Glra2 knockout mice have convincingly demonstrated that GlyR α2 is essential for cortical interneuron migration and progenitor homeostasis. Genetic inactivation of GlyR α2 impairs the capacity of apical progenitors to generate basal progenitors, resulting in an overall reduction of projection neurons in the cerebral cortex. As a result, microcephaly is observed in newborn Glra2 knockout mice, as well as defects in neuronal morphology, increased susceptibility to seizures, and defects in novel object recognition, motor memory consolidation, righting reflexes, novelty-induced locomotion in the open field test, and motivational reward tasks. Consistent with these findings, we and others have identified missense variants and microdeletions in the human GlyR α2 subunit gene (GLRA2) in individuals with autism spectrum disorder (ASD), developmental delay (DD) and/or intellectual disability (ID), often accompanied by microcephaly, language delay and epilepsy. In this review, we highlight the critical role of the GlyR α2 subunit revealed by knockout mice and our current understanding of GlyR α2 pathomechanisms in human NDDs. Finally, we will consider the current gaps in our knowledge, which include: (i) Limited functional validation for GlyR α2 missense variants associated with human NDDs; (ii) The lack of gain-of-function GlyR α2 mouse models; (iii) Our limited knowledge of GlyR α2 interacting proteins. We also highlight potential future developments in the field, including routes to personalized medicines for individuals with GlyR α2 mutations.